A Single Visualization Technique for Displaying Multiple Metabolite-Phenotype Associations - Henglin M.; Niiranen T.; Watrous J.D.; Lagerborg K.A.; Antonelli J.; Claggett B.L.; Demosthenes E.J.; von Jeinsen B.; Demler O.; Vasan R.S.; Larson M.G.; Jain M.; et al. (MDPI, 2022)
To assist with management and interpretation of human metabolomics data, which are rapidly increasing in quantity and complexity, we need better visualization tools. Using a dataset of several hundred metabolite measures profiled in a cohort of similar to 1500 individuals sampled from a population-based community study, we performed association analyses with eight demographic and clinical traits and outcomes. We compared frequently used existing graphical approaches with a novel ` rain plot' approach to display the results of these analyses. The ` rain plot' combines features of a raindrop plot and a conventional heatmap to convey results of multiple association analyses. A rain plot can simultaneously indicate e ff ect size, directionality, and statistical significance of associations between metabolites and several traits. This approach enables visual comparison features of all metabolites examined with a given trait. The rain plot extends prior approaches and o ff ers complementary information for data interpretation. Additional work is needed in data visualizations for metabolomics to assist investigators in the process of understanding and convey large-scale analysis results e ff ectively, feasibly, and practically.